On bridging the gap between theory and practice: a conceptual analysis of practice in relation to a teacher professional learning programme at Stellenbosch University - Jeram, Ramesh (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.